(untitled) (Research, Society and Development, 2020)
This work aimed at evaluating yielding responses of soybean seeds production fields in response to the association between seed vigor level and fertilizer distribution systems at the sowing line.Experimental design was randomized blocks design, with two growing environments (Passo Fundo - RS and Ernestina - RS) x three vigor levels (high = 90%, medium = 70% and low = 60%) x three fertilizer distribution systems (absence, conventional and by transhipment), arranged in four replicates, grain yield (GY). For grain yield (GY), it was applied the method genotype main effects and genotype environment interaction (GGE). Seed vigor levels and fertilizer distribution systems influence on seed yield, first pod insertion height, plant height, number of pods in the main stem and ramifications, magnitude and length of ramifications in soybean.The high vigor level in the conventional and by transshipment fertilization systems provided an absolute increase of 10.9 and 5.6% in seed yield, respectively, in Ernestina-RS. The conventional fertilizer distribution system, in Passo Fundo-RS, increased seed yield in 12.5% in plants originated from low vigor seeds.